Sosialisasi Es Krim Daun Kelor Kaya Antioksidan untuk Peningkatan Imunitas Tubuh dan Rintisan UMKM dalam Rangka Pencapaian SDG’s bidang Kesehatan dan Ekonomi pada Ibu-Ibu Rumah Tangga di Desa Kadipaten, Kecamatan Selomerto, Kabupaten Wonosobo - Pramono, yoyok Budi; Utama, Yos Johan; Werdiningsih, Hermin; Maharani, Arnetta D; Albaari, Ahmad N; Mulyani, Sri; Abduh, Setya Budi M; Hintono, Antonius (Universitas Muhammadiyah Mataram, 2022)
The ongoing Covid-19 case has caused concern for the community. Since the beginning, the appeal to wear a mask, wash hands regularly and maintain immunity has been emphasized. Good body immunity can keep you from being exposed to the Covid-19 virus. Moringa leaves contain antioxidants that can protect the body from free radicals. The antioxidant compounds in Moringa leaves are flavonoids, ascorbic acid, carotenoids and phenolics. This empowerment program is about making Moringa leaf ice cream for housewives in the Kadipaten Village, Wonosobo, which is expected to increase the body's immunity of local residents and can help improve the economy of local residents as well as in the context of achieving SDG's in the health and economic fields